Electronic Information And Educational Environment of the University as a Factor of Implementing The Requirements of the Federal State Educational System for Preparing Future Bachelors of Humanities - Vladimirovich Petrov, Alexey (2021)
The article reveals the content of "electronic information and educational environment" as a pedagogical category. Various approaches to the definition of this concept are shown. The article presents the main objectives of the research, which are as follows: to identify the essential characteristics of the electronic information and educational environment, to determine its functions, to characterize the structural components. Distance learning, as one of the main components of the electronic information and educational environment and as one of the innovative educational models that creates the necessary conditions for providing educational services at any distance, without visiting educational institutions, has a number of advantages: it opens up opportunities for education, regardless of age and geographical location, studying the disciplines of the educational program at your own pace, regardless of time and from other participants in the educational process, self-development based on self-education and self-discipline. Thus, the research hypothesis is determined: the electronic information and educational environment of the University is an effective means of forming the professional competence of students. Theoretical analysis and generalization of scientific and methodological literature were used as research methods. The result of the study was the identification of the essential characteristics of the electronic information and educational environment, advantages and disadvantages. Moreover, the author's interpretation of distance learning and electronic educational resources as the main components of the electronic information and educational environment is proposed.